Independent validation of circulating microRNAs as biomarkers in a case-control study of adolescents with type 1 diabetes for more than 8 years - Diana Swolin-Eide; Auste Pundziute Lyckå; Gun Forsander; Daniel Novak; Johannes Grillari; Andreas B. Diendorfer; Matthias Hackl; Per Magnusson (PLoS ONE, 2026)
MicroRNAs (miRNAs) are epigenetic regulators of gene activity. Analysis of circulating miRNAs enables minimal-invasive studies of disease mechanisms and identification of novel disease biomarkers. The aim of this case-control validation study was to investigate previously identified circulating miRNAs in Swedish adolescents with long-duration (8.0–16.5 years) type 1 diabetes (T1D), and healthy matched controls to confirm their utility as biomarker candidates to diagnose and monitor the progression of T1D. Quantitative PCR analysis of 23 previously reported miRNAs was performed in 24 T1D and 24 control individuals. Body composition was assessed by dual-energy X-ray absorptiometry and peripheral quantitative computed tomography. Prospectively collected clinical data were retrieved from the Swedish diabetes quality registry. The selected miRNAs showed higher variability in both male and female T1D groups compared to controls. Statistical analysis confirmed differences for 12 miRNAs in comparison with controls, including miR-223-3p and miR-135a-5p, which previously were reported to be associated with T1D. MiR-34a-5p and miR-210-3p were positively associated with T1D duration and HbA1c (average from the last year), respectively. In conclusion, 12 previously reported miRNAs showed consistent differential expression between individuals with T1D and controls. Among these were miR-223-3p and miR-135a-5p, which are associated with cardiovascular/inflammatory disease and cancer, respectively. These findings suggest potential clinical utility of circulating miRNAs for T1D diagnosis and disease monitoring, although extended validation of the identified miRNA biomarkers in larger, independent cohorts is required to establish the necessary scientific evidence for clinical translation.